Glycosyl Stille Cross-Coupling with Anomeric Nucleophiles – A General Solution to a Long-Standing Problem of Stereocontrolled Synthesis of C-Glycosides - Zhu, Feng; Yang, Tianyi; Walczak, Maciej A. (Synlett, 2017)
Aryl C-glycosides are common structural motifs found in bioactive natural products and commercially available drugs. Despite their importance, most chemical methods to prepare C-glycosides have relied on the nucleophilic addition/substitution of a glycosyl electrophile, which result in variable anomeric selectivities and yields. Furthermore, these methods are not compatible with saccharides containing free hydroxyl groups. Here, we describe a direct cross-coupling reaction of anomeric nucleophiles (anomeric stannanes) and aryl halides. This method is the first general approach to the synthesis of aryl C-glycosides resulting in exclusive anomeric selectivities for both anomers for a broad range of aryl and carbohydrate coupling partners (including unprotected saccharides).1 Introduction2 Synthesis of Anomeric Stannanes3 Glycosyl Stille Cross-Coupling4 Future Outlook5 Summary
Keywords: anomeric stannanes; anomeric nucleophiles; Stille reaction; C-glycosides; glycosylation